The Protective Effect of Adenosine-Preconditioning on Paraquat-Induced Damage in - Xin Xie; Liangcheng Shang; Sudan Ye; Chun Chen (SAGE Publishing, 2020)
Adenosine plays an important role in the physiological and pathological conditions of the body by combining different types of adenosine receptors widely distributed in various tissues in the body. In present study, an acute model for paraquat-poisoning in Caenorhabditis elegans was established for quantitative assessment via a time-dose-mortality (TDM) modeling technique with various paraquat doses over 8 hours. Adenosine was first used to precondition at high, medium, and low concentrations and the survival rate of C. elegans was recorded to evaluate adenosine antistress protection against paraquat damage. The results revealed that the TDM model was good for the quantitative assessment of paraquat-poisoning on C. elegans based on the Hosmer-Lemeshow test for homogeneity of modeling ( P = .38). The survival rates of adenosine-preconditioned C. elegans have a dose-dependent association with adenosine concentration. At 3000 μM (high concentration) and 300 μM (medium concentration), adenosine-preconditioned C. elegans still had survival rates of 5.38% ± 1.68% and 5.0% ± 1.19% in the subsequent 8 hours observation period. On the contrary, the survival rates of those receiving 30 μM (low concentration) and the 0 μM (unpreconditioned treatment) were zero. To conclude, adenosine preconditioning had protective effects on C. elegans intoxicated with paraquat by decreasing its mortality rate.